Rotação por estações de aprendizagem: possibilidades e desafios na pré-escola - Borges, Vanessa Sant'Ana (2021)
This research is a study about active methodologies with emphasis on the hybrid teaching technique, rotation by learning stations. The main purpose is to identify the conception of this tecnique, check the possibilities and also identify the challenges to develop it with preschool students. The qualitative approach study is guided by bibliographic and documental search - federal legislation and official documents of childhood education- and a literature review derived from researches about the use of the rotation by learning stations on the inicial years of the elementary school. As a the theoretical referential we adopted the contributions of Bacich, Tanzi Neto and Trevisani (2015); Bacich and Moran (2015,2018); Costa (2017); Kenski (2007, 2011); Moran (2010, 2018); Nunes (2017); Silva (2017); Sousa (2018); Tapscott (2010); Valente (2014,2018) and others. The academic relevance of this investigation is the association between the technique and early childhood education, on which we hope to encourage researches, because they still are incipient in Brazil, and produce reflections and practical suggestions to education professionals. As a result, we conclude that digital technologies, as a learning resource, can attract and stimulate the child, like a way to promote autonomy and protagonism in the process of active construction of knowledge and; we propose activities with the use of the technique to the preschool, in order to show the broad possibility of being inserted and integrated into early childhood education.